Authors’ awareness of concepts in the authorship of scientific publications: Viewpoints of the dental faculty in India - Silky Rajesh Punyani; Ashwini Deshpande (Journal of Oral Biology and Craniofacial Research)
Background: There is a great deal of enthusiasm amongst the contemporary dental academicians and researchers to publish their research findings and interesting cases. The competitive atmosphere has fostered a ‘publish or perish’ sentiment following which authors sideline certain essential and valid concepts in authorship and at times resort to unethical behavior knowingly or unknowingly to expand their publication list. Materials and method: We attempted to assess the current knowledge of the Indian dental teaching faculty regarding some important basic concepts in scientific authorship by means of a questionnaire-based pilot study. The respondents were asked questions pertaining to their knowledge of terms such as “authorship criteria”, “conflict of interest”, “plagiarism”, and other authorship issues. Results: Our findings suggested significant lacunae regarding the authors’ understanding of important basic concepts in scientific writing. Conclusion: We suggest possible measures to address this concern and also aim to survey a larger section of the academia in the future.